2004
DOI: 10.1111/j.1365-2133.2004.06054.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled clinical trial of topical photodynamic therapy with methyl aminolaevulinate in the treatment of actinic keratoses in transplant recipients

Abstract: Photodynamic therapy using methyl aminolaevulinate is a safe and effective treatment for actinic keratoses in transplant recipients. It may also reduce the risk of transformation of actinic keratoses to invasive, potentially fatal, squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 25 publications
7
90
0
5
Order By: Relevance
“…Of the 37 post-PDT SCC, 30 (81%) were invasive and 7 (19%) were microinvasive and, of the 48 SCC outside a PDT field, 34 (74%) were invasive and 12 (26.09%) microinvasive. However, no experimental studies have demonstrated an excess risk of developing SCC after PDT in that patient population (14,(27)(28)(29). In addition, as we observed more SCC outside the PDT field than in the PDT field, this emphasizes that our population had a higher risk of SCC development.…”
Section: Resultssupporting
confidence: 49%
“…Of the 37 post-PDT SCC, 30 (81%) were invasive and 7 (19%) were microinvasive and, of the 48 SCC outside a PDT field, 34 (74%) were invasive and 12 (26.09%) microinvasive. However, no experimental studies have demonstrated an excess risk of developing SCC after PDT in that patient population (14,(27)(28)(29). In addition, as we observed more SCC outside the PDT field than in the PDT field, this emphasizes that our population had a higher risk of SCC development.…”
Section: Resultssupporting
confidence: 49%
“…101 MAL-PDT led to complete short-term clearance of treated lesions in >70% of OTRs. 102,103 In addition, over the course of 1 year, a single session of MAL-PDT significantly delayed the appearance of new lesions relative to placebo treatment. 104 Over the longer term (≥2 years), MAL-PDT did not appear to reduce the incidence of AKs 105 or SCCs.…”
Section: Aks In Organ Transplant Recipientsmentioning
confidence: 99%
“…MAL-PDT was statistically more effective than placebo-PDT and more effective than more than one cycle of freezing/thawing with liquid nitrogen spray. 23 Dragieva et al 24 evaluated the efficacy of PDT with MAL in transplant patients. Complete regression of the 129 lesions or a reduction in their number and size occurred in a maximum period of 16 weeks following the end of treatment.…”
Section: Figurementioning
confidence: 99%